Investigation of antioxidant activity of Zoanthus vietnamensis’s crude extract and dichloromethane extract - Phan, Bao Vy; Le Ho , Khanh Hy; Nguyen , Phuong Anh; Doan, Thi Thiet; Pham , Xuan Ky; Dao, Viet Ha (Vietnam Journal of Marine Science and Technology, 2023)
Zoanthid is a potential natural resource with many biological activities, such as antioxidant, antiviral, anti-inflammatory, and cytotoxic activity. Therefore, this study aimed to evaluate the antioxidant activity of 70% ethanol crude extract and dichloromethane fraction from Zoanthus vietnamensis. The total polyphenol content of ethanol and dichloromethane extracts were 19.36 ± 1.37 and 24.95 ± 0.63 mg GAE/g extract, respectively. The DPPH free radical scavenging capacity increased slightly from low to high concentration. The IC50 values reached 9.974 µg/mL and 6.424 µg/mL for ethanol crude and dichloromethane extract. The potassium ferricyanide-reducing power assay result was meager, and the optical density value ranges from 0.015 to 0.105.